Cytotoxic activity of the active fraction from justicia wynaadensis against selected human cancer cell lines - RANJANA RAMESH; DORIN DSOUZA; YOGISHA. S (International Journal of Pharma and Bio Sciences, 2018)
Cancer is the most dreaded disease and the second leading cause of death worldwide. High cost and low efficiency of chemotherapeutic agents towards cancer treatment has encouraged the search for newer, safer and efficient drug. In this regard, herbal products have been extensively exploited as a promising approach for cancer therapy. Thus the present study aimed to evaluate the cytotoxic effect of the active fractions obtained from Justiciawynaadensis against human cancer cell lines. The solvent fractionated active fractions were tested for the cytotoxic effects on lung cancer (A-549), colorectal cancer (HCT116) and breast cancer (MCF-7) cell lines. The results showed that the extract had a higher cytotoxic activity against colorectal cancer cell line HCT-116 than the lung cancer (MCF-7) and breast cancer (A-375) cell lines.